Niveles de comprensión lectora en estudiantes de segundo grado de primaria del distrito de Carmen de La Legua - Abrigo Picón, Delia Rosa (2010)
The purpose of the present research is to identify and compare the levels of reading in students of second grade of Primary Schools from Carmen de la Legua. This job forms a research of descriptive - comparative character and the studying group was formed by 182 students of Public Schools as Bandera de la Paz and Teniente Coronel Perez Salmon and Private Schools as Regina Pacis and B. Group. A comprehensive test of written texts of UMC was taken, Standardized Instrument by the Ministry of Education that makes possible to measure in an objective form, the level of management of reading of second grade students. In conclusion, It doesn´t exist any significant differences of reading comprehension between Public and Private Schools; although they found significant differences in the literal level between boys and girls.